2006
DOI: 10.1167/iovs.05-1181
|View full text |Cite
|
Sign up to set email alerts
|

The Topography of the Central and Peripheral Cornea

Abstract: Highly significant changes occur in the shape of the cornea in the periphery. On average, the peripheral cornea becomes significantly flatter and slightly less astigmatic than the central cornea. A conic section is a poor estimator of the peripheral cornea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(57 citation statements)
references
References 44 publications
(55 reference statements)
6
42
1
1
Order By: Relevance
“…8,1,14,18,25 In our study the trend and pattern of astigmatism in different age groups present results which are comparative with the other Indian and Asian studies. 22,23,26 …”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…8,1,14,18,25 In our study the trend and pattern of astigmatism in different age groups present results which are comparative with the other Indian and Asian studies. 22,23,26 …”
Section: Discussionsupporting
confidence: 56%
“…In different Asian and Indian studies percentage of prevalence varies from 13 per cent to 30% or higher depending on the age or ethnic groups. [13][14][15][16][17] Human infants exhibit both high prevalence and high degrees of astigmatism, largely corneal in origin than in schoolchildren and is also known to vary with ethnicity. 8,12,16,[18][19][20][21] The reported prevalence of astigmatism in children aged 3 to 6 years varies in different studies and in different ethnicities.…”
Section: Discussionmentioning
confidence: 99%
“…11 Corneal astigmatism was classified as being stable, reducing or increasing in the peripheral cornea. Of the subjects with significant corneal astigmatism tested in this study, astigmatism was found most commonly to be reducing (47 per cent of astigmatic subjects) or stable (44 per cent) in the peripheral cornea.…”
Section: Components Of Astigmatismmentioning
confidence: 99%
“…It is important to note that though selective individual ocular component modeling yielded the required levels of myopia and their respective models, all the parameters were found to be within the range of normal values of the population. [53][54][55][56][57][58][59][60] In this experiment, we considered the retinal surface to be a rotationally symmetric aspheric surface for all the myopic models and assumed it to be invariable over the range and types of myopic prescription chosen. The rationale was to limit the degrees of freedom so as to keep the experiment simpler.…”
Section: Discussionmentioning
confidence: 99%